2013
DOI: 10.1111/bjd.12396
|View full text |Cite
|
Sign up to set email alerts
|

T-helper and regulatory T-cell cytokines in the peripheral blood of patients with active alopecia areata

Abstract: The increased levels of serum IL-2, IFN-γ, IL-13 and IL-17A suggested altered T-helper cell function, and reduced serum TGF-β1 levels suggested a defect in Treg function. Therefore, enhanced T-cell-mediated immunity and breakdown of immune tolerance due to deficiency in Tregs may facilitate the occurrence of AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(149 citation statements)
references
References 39 publications
12
123
2
6
Order By: Relevance
“…It has been revealed that SNPs of the IL17RA gene are associated with AA onset age in Korean patients [98]. Serum cytokine levels of IL-17A are significantly increased, and TGFβ1 is significantly decreased, in patients with AA compared with controls [99]. In AA lesions, infiltration of CD4 + IL-17A + T H cells have been found in the dermis, particularly around hair follicles [100] [101].…”
Section: Th17 Cells May Contribute To Alopecia Areata Developmentmentioning
confidence: 99%
“…It has been revealed that SNPs of the IL17RA gene are associated with AA onset age in Korean patients [98]. Serum cytokine levels of IL-17A are significantly increased, and TGFβ1 is significantly decreased, in patients with AA compared with controls [99]. In AA lesions, infiltration of CD4 + IL-17A + T H cells have been found in the dermis, particularly around hair follicles [100] [101].…”
Section: Th17 Cells May Contribute To Alopecia Areata Developmentmentioning
confidence: 99%
“…The main reason for evaluation of Th1 and Th2 cytokine mRNA transcripts was the lack of clear and convincing evidence with respect to the exact role of these cytokines and their contributions in AA pathogenesis [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is controversy in the literature about AA being a Th1 or Th2 autoimmune phenomenon, or both [3][4][5][6]. Thus, identifying the molecular switches that regulate differentiation of CD4+ T cells into Th1 and Th2 effector cells in diseased subjects is the keystone for the characterization of the errors in the function of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Treg hücreler, TGF-β yardımıyla CD4+, CD8+ T hücre ve NK hücre yanıtlarını baskılayarak otoimmün hastalıkların gelişimini engellemektedirler 15 . Alopesi areata hastalarında yapılan çalışmalarda, serum TGF-β1 düzeylerinin düşük olduğu ve bunun Treg hücre fonksiyon bozukluğu ile ilişkili olduğu bildirilmiştir 16 . İmmünomodülatuvar ilaçların Treg hücreleri üzerindeki etkileri hakkında farklı çalışmalar bulunmasına karşın, güncel bir in-vitro çalışmada leflunomidin Treg hücrelerin efektör T hücreleri üzerindeki antiproliferatif etkisini baskıladığı, metotreksatın ve infliksimabın ise böyle bir etkisinin olmadığı bildirilmiştir 17 .…”
Section: Discussionunclassified